Solid Cancers in the Premature and the Newborn: Report of Three National Referral Centers - Anna Raciborska; Katarzyna Bilska; Jadwiga Węcławek-Tompol; Marek Ussowicz; Monika Pogorzała; Joanna Janowska; Magdalena Rychłowska-Pruszyńska; Carlos Rodriguez-Galindo; Ewa Helwich (Elsevier, 2016)
Advances in multidisciplinary care for pediatric cancer have resulted in significant improvement in cure rates over the last decades; however, these advances have not been uniform across all age groups. Cancer is an important cause of perinatal mortality, yet the full spectrum of malignant neoplasms in newborns is not well defined. Methods: The authors have reviewed the clinical features and outcomes of 37 newborns with congenital malignant tumors treated at three referral centers in North, Central, and South Poland between 1980 and 2014. Event-free survival (EFS) and overall survival (OS) rates were estimated by Kaplan-Meier methods and compared using long-rank test and Cox models. Results: Twenty-two patients were diagnosed prenatally. The most common diagnoses were neuroblastoma (48.7%), followed by malignant germ-cell tumor (16.2%), and Wilms' tumor (8.1%). Neuroblastoma was the most common malignancy among full-term infants, and malignant sacrococcygeal teratoma was the most common malignancy in premature infants. Thirty patients (81%) are alive with a median follow-up of 4.8 years from diagnosis. Patients with Wilms' tumor and malignant germ-cell tumors had the best outcomes (5-year OS 100% for both), whereas the worst prognosis was observed for sarcoma patients (5-year OS 72.92%). Premature infants had better outcome than full-term infants (5-year OS 92.8% vs. 72.58%, respectively). Conclusion: Although rare, neonatal cancers can present with an aggressive clinical behavior, but they have a generally good outcome. Early diagnosis and management by expert multidisciplinary teams that integrate perinatal medicine experts with pediatric and surgical oncologists are critical. Centralized care with clear referral pathways that facilitate early initiation of specialized treatment should be prioritized.